High School Social Studies Teachers and their Tactics for Justice - van Kessel, Cathryn; Jones, Kennedy; Plots, Rebeka; Edmondson, Kimberly; Teo, Avery (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2024)
What tactics are high school educators using to teach about socio-political changes in the past and present? Five educators in the province of Alberta (two female, three male; four urban, one rural; four white, one Arab; four without visible religious garb, one Muslim in hijab) explored content they considered to be “radical” and how they teach about (and for) significant socio-political changes toward making society hurt less. Coming from a perspective of symbolic evil, radical love, and radical imagination as inherent to beneficial social movements, the researchers used process and dramaturgical coding to analyze participant insights about decolonial and antiracist education as well as teaching for gender and sexual justice. Participants shared insights about the role of school context and teacher positionality, what might shape an educator to teach for radical change, as well as several tactics: operationalizing positionality, supplementing curriculum, challenging assumptions, subverting school rules, and addressing emotionality.